Cooperative seismic surveys across the Superior–Churchill boundary zone in southern Canada - Green, A. G.; Stephenson, O. G.; Mann, G. D.; Kanasewich, E. R.; Cumming, G. L.; Hajnal, Z.; Mair, J. A.; West, G. F. (Canadian Journal of Earth Sciences, 1980)
Three seismic surveying techniques have been employed in a study of the Superior–Churchill boundary zone in southwestern Manitoba and southeastern Saskatchewan. Two reversed refraction – wide angle reflection profiles, one north–south within the Superior tectonic province and one east–west traversing part of the Superior tectonic province, the boundary zone, and part of the Churchill tectonic province, were used to obtain information on the gross velocity structure of the crust over a large region. Preliminary results from these surveys suggest that the crust beneath the north–south profile is typical of previously published crustal models of the western Superior Province, while the crust beneath the east–west profile is similar to that reported for the Churchill Province in eastern Alberta and western Saskatchewan. Generally, the upper and middle crustal sections in the two tectonic provinces are quite similar, while the lower crust in the Churchill Province has a distinct ~7 km/s layer that is not observed in this part of the Superior Province. In addition, there is a marked thickening of the crust within the boundary zone from ~41 km in the Superior Province to ~46 km in the Churchill Province.A 72 km length of fourfold common reflection point coverage was collected in order to determine the fine structure of the crust over a relatively small region. Reliable stacking velocities that may be used for future processing of the common reflection point data were obtained from an expanding spread reflection survey. Various data processing techniques, including common reflection point stacking, linear and nonlinear velocity filtering, and velocity spectral analysis, have been successful in enhancing reflections from the middle and lower parts of the crust. From the preliminary results of the two reflection surveys, it may be concluded that those parts of the crust which are shown as relatively simple layers in the refraction derived models, may be quite complex when viewed on a smaller scale.